A study of the medical records management practices in selected general hospitals in Manila and Quezon City - Sy, Anthony Jordan L.; Aquino, Aurora (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2004)
The study focused on the current medical records management practices and procedures of three of the largest general hospitals in Metro Manila in comparison to the medical records practices and procedures of a general hospital in amore developed country, the United States.
It was done in order to be able to present an objective overview of the current strengths and weaknesses of medical records management in the respondent Philippine hospitals with the aim of being able to propose or recommend feasible courses of actions that would lead to the improvement of their medical records management programs.
The Philippine general hospitals that were covered by the study include: the Veterans Memorial Medical Center, the Philippine General Hospital and St. Luke's Medical Center. The American Medical Institution that was use as benchmark is the Lancaster Community Hospital, a Joint Commission for the Accreditation of Healthcare organizations (JCAHO) accredited general hospital in Lancaster, California.
For the analysis of the current medical records management programs of the respondent hospitals, survey questionnaires, interviews and ocular inspections were used in order to gather data.
During the course of the study it was found out that the Philippine hospitals' medical records management programs were at par with or even exceed some of the elements of the records management programs of the American benchmark, in terms of records personnel, the records procedure manual, forms and reports management and control as well as records appraisal and retention and disposition schedules.
Though the Philippine hospitals performed well in some aspects of medical records management they fell short of the American benchmark when it came to active and inactive files management and control. This was due to problems with storage space, an increasing number of records being produced.
The study recommends that the Philippine hospitals shift from a decentralized files system to a centralized or a combination system, as well as the development of a suitable inactive records storage area, the acquisition of additional storage areas and the automation of their medical records management program. The study also recommends further lines of study concerning Philippine medical records management.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Medical records -- Management -- Philippines; Records -- Management -- Philippines